ANALISIS SISTEM PENERIMAAN PAJAK PARKIR PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA MANADO - Pamasi, Mira Sakke; Saerang, David P. E.; Afandi, Dhullo (Universitas Sam Ratulangi, 2018)
Parking tax is a local tax imposed under the law number 28 of 2009 on local taxes and user charge. The purpose of this study analyze the adequacyn of the Parking Tax Reception System At the Office of Manado Regional Tax and Retribution Agency. The method used is descriptive analysis. Data were obtained through field studies. The results of this research is the System of Parking Tax Admission in Manado City has been adequate and in accordance with the applicable regulations, namely the Minister of Home Affairs Regulation number 59 at 2007 includes the related functions and documents used as well as the division of tasks and responsibilities. In accordance with the concept of internal control where the collector is divided into several parties that are related and the quality of employees have competence in the field. Therefore, there should be socialization and techincal guidance for employees, especially in the field of accounting for better implementation.Keywords: Parking Tax Reception